ChemInform Abstract: Facile Access to 3, 7‐Dialkyltetrahydro‐1H, 5H‐[1, 2, 4]triazolo[1, 2‐a] [1, 2, 4]triazole‐1, 5‐dithiones. Issue 42 (28th September 2016) - Saeed, Aamer; Channar, Pervaiz Ali; Larik, Fayaz Ali; Floerke, Ulrich
Abstract: The title triazole derivatives are prepared from thiosemicarbazide and aliphatic aldehydes via formation and intramoleculare cyclization of thiosemicarbazone in good yields.